Coupled type waste water treatment device and treatment method of petrochemical secondary effluent - Guo Mingkun; Zhou Yuexi; Wu Changyong (2016)
The invention discloses a coupled type waste water treatment device which comprises a biological aerated filter (7) and a catalytic ozonation tower (14) .The biological aerated filter (7) is in a downward flow mode, and sequentially comprises a first water inlet area (21), a first filler area (22) and a first water outlet area (23) from top to bottom .The catalytic ozonation tower (14) is a sealed tower, and sequentially comprises a second water inlet area (26), a second filler area (27) and a second water outlet area (28) from top to bottom .The sewage deep treatment technology is provided aiming at the urgent technical demand of petrochemical sewage plants in China for upgrading and reconstruction, phosphorus and organic matter can be removed at the same time, and the two units can be coupled. 本发明公开了种耦合式废水处理装置，包括曝气生物滤池(7)和臭氧催化氧化塔(14)，所述曝气生物滤池(7)为下向流式，从上至下依次为第进水区(21)、第填料区(22)、第出水区(23)；所述臭氧催化氧化塔(14)为密封塔，从上至下依次为第二进水区(26)、第二填料区(27)和第二出水区(28)。本发明针对我国石化污水厂面临的迫切的提标改造技术需求，提出的种同时除磷和去除有机物，并能将两个单元耦合的污水深度处理技术。